Adaptasi Instrumen Pengukuran Parental Mediation di Indonesia - Selviana Elisa Sitanggang; Eka Riyanti Purboningsih; Afra Hafny Noer (Universitas Kristen Maranatha, 2022)
Parental Mediation is a guidance for parents to mediate smartphone and tablet usage. The Psychological measurement instruments are needed to know how parents have used strategies to mediate the use of smartphone and tablets to their children. Therefore, this study aims to adapt the Parental Mediation instrument which was developed by Nikken & Schols (2015) to Indonesian version and explore the psychometrics properties. The study involved 305 parents who have children aged 2-6 years old. The sampling technique used in this study was purposive sampling. The adapting process was guided by International Test Commission (2016). The result showed that the adapted Parental Mediation instrument was reliable (α = 0.87) and valid (GFI= 0.976; RMSEA= 0.034; CFI= 0.986; NFI= 0.948; TLI= 0.983; PNFI= 0.788). The result also showed that Indonesian parents use four strategies in mediating the use of smartphone and tablet to their children, there are: Co-use, Supervision, Active-Restrictive Mediation and Technical Mediation.